Internationalisation of Social Work - Neureither, Franziska; Kleibl, Tanja; Lutz, Ronald (Pedagogika Społeczna Nova, 2023)
The article explores the internationalisation of social work from a historical point of view to Indigenous approaches and discusses the concepts of indigenisation, authentication and reconceptualisation. It demonstrates the importance of shifting away from the dominant western perspective on knowledge as well as away from the idea of a universal Social Work and focuses on philosophies and approaches of the Global South. Dialogue as praxis, enablement, and empowerment as well as translation and an ethnological view as methods of internationalisation of Social Work are emphasised. Subsequently, perspectives of Radical as well as Green Social Work and postcolonial feminist approaches within the profession are presented, which can contribute to a desired interwoven, mutually supporting Social Work. The outlook shows the importance of international and cross-cultural exchange between social workers. It emphasizes on sharing of and learning about local methods and practices from other parts of the world, to develop common ideas. In this context self-reflection of the profession and social work- ers is crucially value.